Synthesis, characterization and biological evaluation of cationic porphyrin-terpyridine derivatives - Moura, Nuno M. M. (2017)
A simple access to a new series of cationic porphyrin-terpyridine derivatives is described. The key step to obtain the required neutral precursors as major products involved a Krohnke type approach. The methodology allowed also the isolation of the respective benzoporphyrins and porphyrin-chalcone type derivatives, and in one case a new 2-(2,4-terpyridin-6-yl)-porphyrin. The quaternization of the pyridyl groups was performed in the presence of the adequate alkyl iodide affording the dicationic derivatives in excellent yields. All the new conjugates were fully characterised and it was found that the cationic isomers can be efficiently differentiated by ESI-MS, as their behaviour can be intensively studied by mass spectrometry. The new methylated cationic porphyrin-terpyridine derivatives demonstrate an ability to generate singlet oxygen and their efficacy to photoinactivate bioluminescent Gram-negative E. coli was evaluated. A reduction in the bioluminescence signal, up to 5.4 log, was obtained with the most efficient photosensitiser.